LABOUR CONCERN IN MULTI STORIED BUILDING CONSTRUCTION (International Journal of Engineering Sciences & Management Research, 2019)
India is striding ahead in economic development towards laying emphasis on key industries. Ever since the implementation of the New Industrial Policy of 1991, the concentration has been on industrial development. Liberalisation has been brought into sphere in all activities, with particular attention to promoting over all industrial supremacy. We have a strong presence in the World Trade Organisation (WTO) and are considered to be the representative of Developing Countries. India is regarded as the safe Nation for Foreign Direct Investment (FDI) and Joint Venture (JV) by Multi National Companies. The MNCs are particular in bringing forward the Technology and Capital to India for the prosperity of both themselves and India. This leads to formation of a number of industrial units thereby resulting in phenomenal growth of the outskirts of city. All these give rise excellent employment opportunities for people of all calibre. The wage standard of the industry is also reasonable enabling people possess reasonable disposable income at their end. There is a substantial movement of people from rural areas to city as job seekers. The Construction Industry stands to benefit immensely by this and there have been brisk activities of construction of residential units in the city and outskirts of same. The land cost getting shot up day by day, it is literally impossible for people to construct individual houses. The rent is also prohibitive in the city. People prefer, perhaps, under duress, to own an apartment for themselves by repaying the loan for a longer duration of time, thanks to institutional finance.